Mineral requirements for growth of Moxoto goats grazing in the semi-arid region of Brazil - Araujo, M. J.; Medeiros, A. N.; Teixeira, I. A. M. A. [UNESP]; Costa, R. G.; Marques, C. A. T.; Resende, Kleber Tomás de [UNESP]; de Melo, G. M. P. [UNESP] (Elsevier B.V., 2010)
Indigenous goats play an important role in the semi-arid region of Northeastern Brazil as a biological resource with great genetic variability and historical value. In addition, they are a source of animal protein of high biological value, available to people of low income. However, there is a lack of information about these animals, mainly regarding their nutritional requirements. Therefore, the objective of this study was to determine net requirements of Ca, P, Mg, Na and K for growth of 36 male Moxoto goat kids (15.69 +/- 0.78 kg initial BW), grazing in the semi-arid region of Brazil. Four kids were slaughtered at the beginning of the experiment (baseline group, 15.37 +/- 0.30 kg BW) and the remainder (n = 32) were allocated randomly to one of the four levels of concentrate supplementation (treatments groups: 0, 0.5, 1.0 and 1.5% BW), with eight kids per group. When the animals in the 1.5% BW treatment group reached 25 kg BW, the animals in the other treatment groups were also slaughtered. The individual whole empty body was weighed, ground, mixed and sampled for chemical analyses. The body composition (g/kg empty body weight; EBW) ranged from 10.80 to 11.50 g Ca; 7.86 to 8.74 g P; 0.37 to 0.42 g Mg; 1.57 to 1.61 g Na and 1.58 to 1.74 g K, for Moxoto kids at 15 and 25 kg BW. The net mineral requirements (g/kg empty weight gain; EWG) were determined by comparative slaughter technique which ranged from 9.53 to 10.65 g Ca; 7.41 to 8.65g P; 0.36 to 0.43g Mg; 1.31 to 1.41 g Na and 1.47 to 1.70g K for animals with BW ranging from 15 to 25 kg. In conclusion, our study indicated that indigenous goats grazing in the semi-arid region of Brazil have different mineral requirements from those values recommended by international committees for dairy and meat goats. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Body composition; Caatinga; Indigenous goat; Supplementation